2022
DOI: 10.32598/ijpcp.27.4.3067.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Integrated Cognitive-Behavioral Therapy and Transdiagnostic Treatment on Symptoms of Patients with Generalized Anxiety Disorder Comorbid with Depression

Abstract: Objectives The purpose of this study was to compare the efficacy of integrated cognitive behavioral therapy with Transdiagnostic Treatment on symptoms of patients with generalized anxiety disorder comorbid with depression. Methods The quasi-experimental design of two groups (integrated cognitive behavioral therapy group, Transdiagnostic treatment group) was used for competitive validity. The statistical population included people with comorbid anxiety disorder with depression who referred to counseling centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…[ 3 ] The results of epidemiological studies of psychological disorders show that anxiety disorders and depression are the most common psychological disorders; at the same time, the fourth most common disorder following phobia, substance-dependent disorder, and depressive disorders is obsessive-compulsive disorder. [ 19 20 21 22 23 24 25 26 27 28 ] The high prevalence of comorbidity of anxiety disorders, and depression with comorbidity is reported between 40% and 80%[ 29 ] and also people with obsessive-compulsive disorder often suffer from other mental disorders. Several adults with this disorder have a lifetime diagnosis of an anxiety disorder (76% such as panic disorder, social anxiety disorder, generalized anxiety disorder, or specific phobia) or bipolar disorder (63% with bipolar or any other type of depression), the most common of which is major depressive disorder (41%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] The results of epidemiological studies of psychological disorders show that anxiety disorders and depression are the most common psychological disorders; at the same time, the fourth most common disorder following phobia, substance-dependent disorder, and depressive disorders is obsessive-compulsive disorder. [ 19 20 21 22 23 24 25 26 27 28 ] The high prevalence of comorbidity of anxiety disorders, and depression with comorbidity is reported between 40% and 80%[ 29 ] and also people with obsessive-compulsive disorder often suffer from other mental disorders. Several adults with this disorder have a lifetime diagnosis of an anxiety disorder (76% such as panic disorder, social anxiety disorder, generalized anxiety disorder, or specific phobia) or bipolar disorder (63% with bipolar or any other type of depression), the most common of which is major depressive disorder (41%).…”
Section: Discussionmentioning
confidence: 99%
“…;[ 25 ]4 people, ghaderi et al . [ 26 ]10 people. So, in this research, the optimal number of people is suggested between 6 and 10.…”
Section: Methodsmentioning
confidence: 99%
“…In this formula, the pre-test score is subtracted from the post-test score and the result is divided by the pre-test score. Then, the result is multiplied by 100 (Hamidpour et al, 2011).…”
Section: Program Descriptionmentioning
confidence: 99%